2013
DOI: 10.1353/rhe.2013.0040
|View full text |Cite
|
Sign up to set email alerts
|

Marginalizing Merit?: Gender Differences in Black Faculty D/discourses on Tenure, Advancement, and Professional Success

Abstract: Little work has addressed the ways in which race and gender intersect and shape Black professors' experiences as they seek professional advancement. Framed by critical race theory, this qualitative study uses discourse analysis to analyze the narratives of 28 Black professors employed at two research universities. Findings suggest that faculty perceive race and gender influencing their evaluations for academic advancement , with key gender distinctions in discourses about teaching and service in relation to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 49 publications
4
99
0
Order By: Relevance
“…Student bias against Black faculty can influence tenure, given how course evaluations can be a heavily weighted tenure criterion. Consequently, Black faculty are less likely to be promoted and tenured than White faculty (Bradley & Holcomb-McCoy, 2004;Griffin, Bennett, & Harris, 2013). Although multiple factors are considered for tenure, the feedback Black faculty receive from colleagues and students is critical.…”
Section: Black Faculty Pursuit Of Tenurementioning
confidence: 99%
“…Student bias against Black faculty can influence tenure, given how course evaluations can be a heavily weighted tenure criterion. Consequently, Black faculty are less likely to be promoted and tenured than White faculty (Bradley & Holcomb-McCoy, 2004;Griffin, Bennett, & Harris, 2013). Although multiple factors are considered for tenure, the feedback Black faculty receive from colleagues and students is critical.…”
Section: Black Faculty Pursuit Of Tenurementioning
confidence: 99%
“…The emotional challenges of underrepresentation are exacerbated by more forms of oppression prevalent in homogenous institutions. Scholarship on predominantly White research-intensive colleges and universities has found minoritized faculty disproportionately encounter (a) subtle discrimination and microaggressions (Eagan & Garvey, 2015); (b) cultural taxation, tokenism, and erasure (Dancy & Jean-Marie, 2014); (c) challenges to expertise and scholarly competence (Joseph & Hirshfield, 2013); (d) bias in recruitment, promotion, and tenure (Gasman et al, 2015); and (e) gendered, racialized, and ableist systems of merit (Griffin, Bennett, & Harris, 2013). In the current study, we illustrate encounters with three of these institutional forms of oppression, continuing the conversation on minoritized faculty experiences and focusing it on counselor education.…”
Section: Institutional Oppression In Academiamentioning
confidence: 99%
“…Authenticity and vulnerability invite some students to take faculty less seriously because they have been socialized to see faculty as distant and impersonal, and when this does not happen, they assume the faculty lack credibility (Tuitt, 2003). Additionally, when some faculty engage authentically with students while others in the same program do not, they may bear additional service and mentoring responsibilities (Griffin, Bennett, & Harris, 2013). The responsibility for engaging with students of color in an authentic way cannot be solely the responsibility of faculty of color in graduate programs.…”
Section: Authenticitymentioning
confidence: 99%